Navigating complexity: a multifaceted approach to teaching climate change in middle school - Durak, Benzegul; Topcu, Mustafa Sami (ROUTLEDGE JOURNALS, TAYLOR & FRANCIS LTD, 2024)
Global climate change is one of the most significant challenges of the twenty first century, requiring its integration into K-12 science education curricula to foster informed and climate-literate citizens. However, challenges remain in effectively teaching climate change, including a lack of instructional materials and a reliance on traditional teaching methods that limit student engagement and understanding. To address these challenges, this study developed a unit that combines socioscientific issue-based instruction, scientific modeling, and systems thinking to improve climate education. The unit was implemented by a teacher trained in the Socioscientific Issues and Model-based Learning (SIMBL) framework and showed promising results. Students demonstrated an improved understanding of climate complexity, as evidenced by the inclusion of multiple factors in their system maps and the justification of policy decisions based on their knowledge. In addition, the integration of media literacy tools improved students' critical engagement with online content. Overall, the SIMBL unit facilitated transformative learning experiences that empowered students to understand and address the multifaceted challenges of climate change. The study suggests implications for teachers and advocates for adapting the sequence to various standards and socioscientific topics beyond climate change.
Keywords: Climate change; socioscientific issue; modeling; model-based learning; ISSUES; Education & Educational Research